Living in the darkness: a new cave cricket species of the genus Endecous Saussure (Orthoptera, Grylloidea, Phalangopsidae) from Serra da Bodoquena in Mato Grosso do Sul state, Brazil - de Campos, Lucas Denadai; Bolfarini, Márcio Perez; Suemitsu, Mônica Midori [UNESP]; Borghezan, Lívia Medeiros Cordeiro; Souza-Dias, Pedro G.B. (Magnolia Press, 2023)
We describe a new species of the genus Endecous Saussure (1878), recorded at the Dente de Cão and Urubu Rei caves, which are located in the Bodoquena municipality, state of Mato Grosso do Sul, Brazil. Species of Endecous are the most common of crickets in Brazilian hypogean environments. Endecous comprises 24 species described and is widely distributed throughout South America, occurring also in Argentina, Bolivia and Uruguay. We also present a brief discussion about the presence of the genus in subterranean environments and a distribution map of Endecous troglobitic species through the regions of the Brazilian karst.
Keywords: distribution; Hypogean; new taxa; troglobitic